2024
DOI: 10.1037/tra0001249
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time since index trauma on trauma-related beliefs.

Abstract: Objective: Greater duration of negative trauma-related beliefs may inhibit improvements in these cognitions during posttraumatic stress disorder (PTSD) treatment. The goal of the current study was to examine the impact of time since trauma on change in negative trauma-related beliefs during PTSD treatment. Method: A sample of 126 adults diagnosed with PTSD were randomized to Cognitive Processing Therapy (CPT) or Written Exposure Therapy (WET) and completed the Posttraumatic Cognitions Inventory (PTCI) at pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…As several variables were not normally distributed and transformations did not improve normality, bootstrapping (5000 bootstrapped samples) were used for all analyses. Due to group differences in age and education and potential influences of trauma type and time since trauma on findings[e.g., 68 , 69 , these variables were included as covariates in all analyses. Following current recommendations 70 , anxiety and depression were not included as covariates but were rather used to provide further details about the sample.…”
Section: Methodsmentioning
confidence: 99%
“…As several variables were not normally distributed and transformations did not improve normality, bootstrapping (5000 bootstrapped samples) were used for all analyses. Due to group differences in age and education and potential influences of trauma type and time since trauma on findings[e.g., 68 , 69 , these variables were included as covariates in all analyses. Following current recommendations 70 , anxiety and depression were not included as covariates but were rather used to provide further details about the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we are not gathering information on trauma characteristics such as the ages at which the trauma was experienced, the frequency or chronicity of each experienced trauma, or the time since the trauma has elapsed. Such information can impact posttrauma distress [78][79][80] and may moderate the impacts of PPMT in this study; hence, it should be empirically investigated in future research. In addition, while the research design of one assessment per day enables examination of changes in daily symptoms, affect, and cognition before and after the intervention, it does not have a sampling frequency nor sufficient power to examine fine-grained dynamic interactions between symptoms, affect, and cognition using even more complex modeling techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, negative posttrauma cognitions are an important trauma-related outcome that is frequently studied alongside PTSD symptoms (Brown et al, 2019;Schumm et al, 2015). A recent study found that for CPT and, to a lesser extent, written exposure therapy, longer TST was associated with less improvement in negative trauma-related beliefs; this, however, is the only study to our knowledge that has assessed this association (Cole et al, 2022). Given that negative posttrauma cognitions are a construct related to yet distinct from PTSD, it is important to further investigate whether longer TST causes these beliefs to become more deeply ingrained, thus potentially less likely to change in intensive treatment.…”
mentioning
confidence: 99%
“…Whereas some individuals may seek help shortly after symptom onset, others may live with PTSD and related symptoms for decades following trauma exposure. In a recent study, the average time since trauma (TST) in a sample of adults diagnosed with PTSD was approximately 18 years, with a range of 2 months to 57 years, demonstrating that individuals may seek PTSD treatment at vastly different times following trauma exposure (Cole et al., 2022). Previous research on the role of TST on PTSD treatment outcomes has been inconclusive, and findings are dependent on treatment type.…”
mentioning
confidence: 99%